2017
DOI: 10.1021/acs.analchem.7b02329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DMSO on Protein Structure and Interactions Assessed by Collision-Induced Dissociation and Unfolding

Abstract: Given the frequent use of DMSO in biochemical and biophysical assays, it is desirable to understand the influence of DMSO concentration on the dissociation or unfolding behavior of proteins. In this study, the effects of DMSO on the structure and interactions of avidin and Mycobacterium tuberculosis (Mtb) CYP142A1 were assessed through collision-induced dissociation (CID) and collision-induced unfolding (CIU) as monitored by nanoelectrospray ionization-ion mobility-mass spectrometry (nESI-IM-MS). DMSO concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…[32][33][34] Moreover, we found that these three aprotic solvents can also cause signal broadening ( Figure S3) that represents the formation of solvent adducts. This finding is similar with previous reports on DMSO, 16,17 which can protect against the dissociation of protein by reducing coulomb repulsions due to the low charge state and cooling effect of adduct dissociation.…”
Section: Effects Of Aprotic Solvents On the Dissociation And Chargisupporting
confidence: 93%
See 3 more Smart Citations
“…[32][33][34] Moreover, we found that these three aprotic solvents can also cause signal broadening ( Figure S3) that represents the formation of solvent adducts. This finding is similar with previous reports on DMSO, 16,17 which can protect against the dissociation of protein by reducing coulomb repulsions due to the low charge state and cooling effect of adduct dissociation.…”
Section: Effects Of Aprotic Solvents On the Dissociation And Chargisupporting
confidence: 93%
“…And the relative abundance of dimer and monomer of apo‐SOD1 could be evaluated by using the extracted corresponding IM spectrum. The bimodal effect of DMSO on protein charging has been well documented, and its effect on the structure of protein is highly protein dependent . In the current study, the effects of aprotic solvents on the charging and dimer dissociation of apo‐SOD1 are shown in Figures D,E and S1 and S2.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…[126][127][128] DMSO has also been used as a (co)solvent for NOM, where it has been found to increase the quantity of humin recovered by the standard alkaline extraction method, 31 the diversity of organic matter obtained by alkaline extraction of soils and sediments, 129 and the quantity of hydrophobic moieties detected during structural characterization of NOM by high resolution NMR. 125 Analogous benets from the solvency of DMSO have been reported in studies of proteins, including reducing binding affinities of proteins, 130 protein unfolding, 131,132 DMSO affecting protein charge, 130 and aiding in electron transfer. [133][134][135] While mediators and aprotic solvents can greatly improve the electrode response of polyelectrolytes like proteins and NOM, other advances in electrochemical methodology can also have signicant benets.…”
Section: Introductionmentioning
confidence: 90%